The Impact of Diet on Male Fertility - Serkis, Barbara; Bentkowska, Zuzanna; Miazga, Małgorzata; Celichowska, Magdalena; Bogoń, Aleksandra; Golemo, Jagna; Kałuża, Izabela; Szpyra, Justyna; Dębińska, Julia; Dziuba, Gabriela (Quality in Sport, 2024)
Introduction: Infertility is a reproductive health issue where the inability to conceive after 12 months of regular unprotected intercourse affects about 8 to 12% of couples of reproductive age. Factors such as diet, lifestyle, and exposure to toxins can negatively impact men's reproductive capacity, including semen parameters and gonadal function. The impact of diet on male fertility, including hormone levels and the process of spermatogenesis, is the subject of intense research. Aim of the Study: This study aims to review current scientific research on the impact of diet on male fertility to provide updated knowledge on this topic, essential for preventive and therapeutic actions in this field. Materials and Methods: A comprehensive review of scientific and medical literature was conducted using PubMed and Google Scholar databases. The search terms included: impact of diet on male fertility, impact of diet on semen parameters, impact of diet on semen quality, male fertility, diet and male fertility, types of diets and fertility. Conclusion: Diet plays a crucial role in male fertility, affecting semen quality. It is recommended to consume meat in moderation, especially organic, and to increase the intake of fish rich in omega-3 while avoiding contaminants. Regular consumption of fruits, vegetables, and grains improves semen parameters, while limiting sweets, sugary drinks, and alcohol, as well as quitting smoking, is beneficial for reproductive health. Men planning fatherhood should also consider reducing cannabis use. Future research should focus on the impact of individual dietary factors on male fertility.